(untitled) (City: History, Culture, Society, 2023)
The article delves into the portrayal of the Kyiv text in Bohdan Boychuk’s novel Rozanna z Nyvok (Rosanna from Nyvky). Using the theories of Tamara Hundorova, the author of the article correlates the characteristics of a modern "romance" urban text (the Kyiv text in particular) and kitsch, which allows classifying Rozanna z Nyvok within "naive, or unconscious, kitsch," according to Tamara Hundorova. The corresponding manner of Boychuk’s text is manifested in the affinity of its form and plot with the romance genre, as well as in the specific method of the author’s narration. The paper examines the depiction and subsequent transformations of Kyiv’s landscape in Rozanna z Nyvok. In addition, the work outlines the landmarks that are constant in marking urban space. A key finding is the novel’s depiction of Kyiv’s space as insular, frequently highlighting locales (such as Volodymyrska Hill, nearby areas like St. Sophia’s and St. Michael’s Cathedrals, and the Golden Gate) that contribute to Kyiv’s imagological representation. Notably, the text includes inaccuracies common among those unfamiliar with the city, like wrongly mapped routes and misnamed streets. This aspect ties into both the novel’s protagonist and Boychuk’s own limited experience living in Kyiv. While preserving the sentiment for the sacred monuments of the city, the novel shifts the focus to the secular. It restructures the narrative space around non-historic sites like restaurants and cafes within various districts. Simultaneously, as the novel’s protagonist evolves emotionally, the scope of the Kyiv setting broadens to include more distant locales, such as the vicinity of the Arsenalna metro station and Peremohy Avenue in the Nyvky area. Since the impetus for such a change is the development of the protagonist’s romantic feelings, it becomes evident that the Kyiv space is life-affirming, and leaving it becomes a sign of death or ageing.